Structural basis of membrane engagement and polyreactivity control in HIV-1 MPER broadly neutralizing antibodies - So Yeon Cho; Kimmo Rantalainen; Gabriel Ozorowski; Danny Lu; Ryan Tingle; Wen-Hsin Lee; Andrew B. Ward; William R. Schief; Ian A. Wilson (Proceedings of the National Academy of Sciences, 2026)
The membrane-proximal external region (MPER) of HIV-1 Env represents a critical target for broadly neutralizing antibodies (bnAbs) due to its conservation and functional importance. However, MPER-targeting bnAbs recognize composite epitopes comprising peptide and viral membrane lipid components, creating an inherent tension between viral neutralization efficacy and polyreactivity. 10E8-class antibodies exhibit high neutralization potency with low polyreactivity, whereas 4E10-class antibodies show comparably broad neutralization but higher polyreactivity, underscoring the need to understand the structural basis of this distinction. We therefore determined crystal structures of DH511.1 (memory B cell–derived), DH511.12P (plasma cell-derived), and VRC42.01 in complex with MPER peptide and phosphatidic acid, along with a cryo-EM reconstruction of DH511.2 bound to membrane-embedded Env. Through integrative analysis taking into account previously determined structures of other MPER bnAbs, we reveal two distinct lipid recognition strategies. Groove-mediated binders, including 10E8 and DH511, engage lipids through antibody–membrane interface grooves with distinct geometries and angular approaches to the membrane. In contrast, heavy chain-mediated binders, including 4E10, PGZL1, and VRC42, utilize positively charged CDR H1 patches for direct lipid headgroup recognition. Importantly, DH511 lineage members exhibited differential cardiolipin polyreactivity linked to their maturation stage. PGZL1 and VRC42.01 employ weaker positive patches at lipid-binding sites than 4E10, and PGZL1 additionally introduces a CDR H3-mediated negative patch that creates electrostatic repulsion with negatively charged lipid headgroups, thereby limiting nonspecific interactions. These findings provide a structural framework for understanding how MPER bnAbs balance lipid binding with specificity and inform immunogen design for inducing safe and effective neutralizing responses.